(3GdcGTa aj eYQaI CSeGA GdQLGds - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GdMGaX GdeRj , jhSa Hf YHO GdQMef Hf jhSa LeGd GdOjf GdRcj CHh eMeO GdbVGYj GdcdHj, LeGd GdOjf CHh GdMLGL GdMGaX GdeRj,J (B742 (3g` s ((3CMeO Hf eMeO Hf MjOQI GdOLhi GdeUQi s)
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ ddg s
(3fSNI fbdkG Yf fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs